PRINCIPAL'S LEADERSHIP STRATEGY IN THE DEVELOPMENT OF TEACHER PROFESSIONALISM - Achadi Budi Santosa (Universitas Negeri Malang, 2022)
Abstract: This study aims to determine the implementation of the principal's strategy in developing teacher professionalism, teacher professionalism is needed to obtain good quality output. This research is motivated by the importance of education in supporting the future development of the nation and developing the potential of students in facing global competition. The method used in this research is a qualitative case study approach. Sources of data obtained from teachers, data collection through observation, interviews and documents. Data analysis used qualitative data analysis model of Miles and Huberman. The results of this study reveal that the principal's strategy in improving teacher professionalism is carried out through; (1) formulating school planning and development (2) improving teacher work discipline, both in terms of learning, administration, and behavior; (3) conducting regular academic supervision; and (4) collaborate with supervisors, committees, parents, and government agencies.Keywords: principal leadership; academic supervision; teacher professionalism Abstrak: Penelitian ini bertujuan untuk mengetahui implementasi strategi kepala sekolah dalam mengembangkan profesionalisme guru, profesionalisme guru sangat dibutuhkan untuk mendapatkan output yang berkualitas. Penelitian ini dilatarbelakangi oleh pentingnya pendidikan dalam mendukung pembangunan masa depan bangsa dan mengembangkan potensi peserta didik dalam menghadapi persaingan global. Metode yang digunakan dalam penelitian ini adalah pendekatan studi kasus kualitatif. Sumber data diperoleh dari guru, pengumpulan data melalui observasi, wawancara dan dokumen. Analisis data menggunakan model analisis data kualitatif Miles dan Huberman. Hasil penelitian ini mengungkapkan bahwa strategi kepala sekolah dalam meningkatkan profesionalisme guru dilakukan melalui; (1) merumuskan perencanaan dan pengembangan sekolah (2) meningkatkan disiplin kerja guru, baik dalam hal pembelajaran, administrasi, maupun perilaku; (3) melakukan supervisi akademik secara berkala; dan (4) bekerjasama dengan pengawas, panitia, orang tua, dan instansi pemerintah..Kata kunci: kepemimpinan kepala sekolah; supervisi akademik; profesionalisme guru